(untitled) (Mediscope, 2020)
Background: Elective or emergency caesarean sections are routinely done under spinal anaesthesia (SA) with bolus dose of local anaesthetic drugs. Objective: To compared fractionated dose with bolus dose in SA for haemodynamic stability and duration of analgesia in patients undergoing elective lower segment caesarean section (LSCS). Methods: The present study was carried out in the Department of Anaesthesiology, Ad-din Akij Medical College Hospital, Khulna from January 2018 to December 2018 on sixty female patients (thirty in each group) of the American Society of Anesthesiologists physical status I–III, age from 18 to 40 years, height from 140 to 180 cm, singleton pregnancies scheduled for elective LSCS under SA. Patients with pre-existing diseases or pregnancy-induced hypertension, cardiovascular or cerebrovascular disease, any contraindication to SA, those weighing <50 kg or >110 kg and those taller than 180 cm or shorter than 140 cm and severely altered mental status, spine deformities or history of laminectomy were excluded from the study. Results: The mean duration of analgesia was statistically significant (p<0.05) between two groups. Mean pulse rate- after 5 min, after 10 min, after 15 min, after 30 min, after 45 min and after 60 min were significantly (p<0.05) higher in group F than group B. Mean arterial pressure- before given study drug, after 0 min, after 5 min, after 10 min, after 15 min, after 30 min, after 45 min and after 60 min were not significantly (p>0.05) between two group. 14 patients (46.7%) in group B and 5 patients (16.7%) in group F required vasopressor. The difference was significant (p<0.05) between two groups. Conclusion: Separation process in which a certain quantity of a mixture dose of SA provides better haemodynamic stability and longer period of analgesia compare to bolus dose in patients undergoing elective caesarean section. Mediscope Vol. 7, No. 2: July 2020, Page 95-102